La L’EFFICACITÉ DE LA PUBLICITÉ IMPRIMÉE FRANÇAISE COMME UN MEDIA D’APPRENTISSAGE DE L’ÉCRITURE - Rizqina, Aulia; Agustinigrum, Tri Eko; Widayanti, Diah Vitri (Didacticofrancia: Journal Didactique du FLE, 2016)
The purpose of this study was to determine the effectiveness of the use of advertising in learning to enhancing the ability of simple dialogue and descriptive paragraphes writing aboutdonner et demander des informations et des opinions sur le vêtement for students of eleventhclass of SMA Negeri 2 Ungaran.This research is a quasi-experimental. The design used in thisstudy was pretest-posttest. The sample in this study is purposive sampling technique. Data collection methods used in this research is the documentation method and test method. Validitywas used in this study to measure the content validity and the reliability of the method usedto measure the test-retest that the results correlated with product-moment formula. Data wereanalyzed by t-test formula. From the calculation results, tcount = 10,61 and ttable = 1,72.Because tcountis greater than ttable, French-language printed ads was effective in improvingwriting skills of dialogue and descriptive paragraphes about donner et demander des informations et des opinions sur le vêtement in eleventh class of SMA Negeri 2 Ungaran.